2016
DOI: 10.1016/j.ajhg.2016.09.023
|View full text |Cite
|
Sign up to set email alerts
|

HLA-C Level Is Regulated by a Polymorphic Oct1 Binding Site in the HLA-C Promoter Region

Abstract: Differential HLA-C levels influence several human diseases, but the mechanisms responsible are incompletely characterized. Using a validated prediction algorithm, we imputed HLA-C cell surface levels in 228 individuals from the 1000 Genomes dataset. We tested 68,726 SNPs within the MHC for association with HLA-C level. The HLA-C promoter region variant, rs2395471, 800 bp upstream of the transcription start site, gave the most significant association with HLA-C levels (p = 4.2 × 10). This imputed expression qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 39 publications
(43 reference statements)
0
64
0
Order By: Relevance
“…The presence of an A nucleotide in place of a G at this position was associated with higher Oct‐1 binding and transcriptional activity. This association was confirmed in a genome‐wide expression quantitative trait analysis of HLA‐C mRNA levels determined by qPCR of peripheral blood mononuclear cell RNA from 273 individuals . Interestingly, the group of HLA‐C alleles that have the highest level of expression ( HLA‐C*01 , *04 , *06 , *12 , and *14 ), all possess the A residue associated with higher promoter activity .…”
Section: Upstream Elementsmentioning
confidence: 70%
See 2 more Smart Citations
“…The presence of an A nucleotide in place of a G at this position was associated with higher Oct‐1 binding and transcriptional activity. This association was confirmed in a genome‐wide expression quantitative trait analysis of HLA‐C mRNA levels determined by qPCR of peripheral blood mononuclear cell RNA from 273 individuals . Interestingly, the group of HLA‐C alleles that have the highest level of expression ( HLA‐C*01 , *04 , *06 , *12 , and *14 ), all possess the A residue associated with higher promoter activity .…”
Section: Upstream Elementsmentioning
confidence: 70%
“…A study of SNPs associated with the level of HLA-C mRNA expression identified an SNP in a predicted Oct-binding site 800 bp upstream of the transcription start site as being highly associated with differences in HLA-C expression between alleles. 37 The presence of an A nucleotide in place of a G at this position was associated with higher Oct-1 binding and transcriptional activity. This association was confirmed in a genome-wide expression quantitative trait analysis of HLA-C mRNA levels determined by qPCR of peripheral blood mononuclear cell RNA from 273 individuals.…”
Section: The −800 Enhancer Regionmentioning
confidence: 93%
See 1 more Smart Citation
“…We have shown previously that a polymorphic microRNA (miRNA) binding site in the 3’UTR of HLA-C contributes to allele-specific variation in expression levels and associates with both human immunodeficiency virus (HIV) viral control and risk of Crohn’s disease independently of individual HLA allelic effects(1). More recently, a variant in an Oct1 binding site 800bp upstream of the HLA-C coding region was also shown to regulate HLA-C expression levels(2), and this variant along with the polymorphic miRNA binding site account for 40% of the differential cell surface expression levels of HLA-C. Thus, variation in regulatory regions of the HLA class I loci that affect their expression levels may influence the immune response and disease susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it contains a rs2395471G allele which leads to low expression. 26 Nevertheless, the net result of these three polymorphisms is rather high expression on the cell surface. 24,25 Therefore, HLA-C*05:01 has a potential for efficient presentation of bound peptides.…”
Section: Discussionmentioning
confidence: 99%